2012
DOI: 10.1093/mp/sss041
|View full text |Cite
|
Sign up to set email alerts
|

BZS1, a B-box Protein, Promotes Photomorphogenesis Downstream of Both Brassinosteroid and Light Signaling Pathways

Abstract: Photomorphogenesis is controlled by multiple signaling pathways, including the light and brassinosteroid (BR) pathways. BR signaling activates the BZR1 transcription factor, which is required for suppressing photomorphogenesis in the dark. We identified a suppressor of the BR hypersensitive mutant bzr1-1D and named it bzr1-1D suppressor1-Dominant (bzs1-D). The bzs1-D mutation was caused by overexpression of a B-box zinc finger protein BZS1, which is transcriptionally repressed by BZR1. Overexpression of BZS1 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
146
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(152 citation statements)
references
References 44 publications
4
146
0
2
Order By: Relevance
“…Studies have detailed the mechanisms involved in hypocotyl cell elongation regulated by light, phytohormones, and transcription factors (Wang et al, 2002;Niwa et al, 2009;Luo et al, 2010;Fan et al, 2012). In addition, a recent study showed that pectin-dependent cell wall homeostasis is important for BR regulation of hypocotyl growth (Wolf et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have detailed the mechanisms involved in hypocotyl cell elongation regulated by light, phytohormones, and transcription factors (Wang et al, 2002;Niwa et al, 2009;Luo et al, 2010;Fan et al, 2012). In addition, a recent study showed that pectin-dependent cell wall homeostasis is important for BR regulation of hypocotyl growth (Wolf et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…65,71 Independent experiments demonstrate that BBX21, BBX22 and BBX24 have transactivating capacity in transcriptional systems, 44,45,51,60 although no DNA binding ability has been described. The proposed mechanism of action uses the interaction with other transcription factors that bind to DNA, such as HY5 and HYH (Fig.…”
Section: The Role Of Subfamily IV Bbx Proteinsmentioning
confidence: 99%
“…However, it is still not known if BBX20 has a role in karrikindependent germination responses. Fan et al 71 described the function of BBX20 as a negative regulator of brassinosteroid (BR) signaling, but a positive regulator of photomorphogenesis. The authors found that BBX20 is regulated transcriptionally via BR signaling (by BZR1), and posttranscriptionally by means of a COP1-dependent mechanism, 71 similarly to GATA2 regulation.…”
Section: The Role Of Subfamily IV Bbx Proteinsmentioning
confidence: 99%
See 2 more Smart Citations